Efficiency analytical of five-phase induction motors with different stator connections for fracturing pump drives. (November 2022) - Fan, Shuting; Meng, Dawei; Ai, Mengmeng
Abstract: Improving the efficiency of fracturing pump drive motors is key to improving the performance of fracturing equipment. For this purpose, this paper investigates the losses and efficiency of five-phase fracturing pump drive motors with different stator winding connections. Inverters generate different phase voltages in different stator winding connections, which leads to different spatial harmonics and losses. Of the various losses in the motor, the iron loss is hard to measure. Component theory is proposed, and a corresponding equivalent circuit is developed in this paper. Calculation of the iron loss based on the phase voltage of the different stator winding connections. In order to verify the validity of the equivalent circuit, the proposed model was simulated in MATLAB/Simulink and some experimental tests were carried out on several 15 kW motors. The results show that the total harmonic distortion (THD) coefficient of voltage and current is the smallest for the pentacle winding in the single winding, the voltage, and current THD coefficient is the smallest for the pentagon–star winding in the combine d winding. And according to the efficiency calculation, it can be seen that the fracturing pump drive motor with the pentagon–star winding is highly efficient and energy-saving, as well as having a high fault tolerance.